Brassica napus BnaWIP2 transcription factor promotes seed germination under salinity stress by repressing ABA biosynthesis and signaling - Shuangcheng He; Saiqi Yang; Yuanchang Min; Ankang Ge; Junjin Liu; Zijin Liu; Yuan Guo; Mingxun Chen (Crop Journal)
Rapeseed (Brassica napus L.) is a global oil crop. Salinity stress impedes the growth of rapeseed, especially during seed germination. The key genes mediating salinity stress response during seed germination in B. napus remain largely unknown. Here, we found that all six paralogs of C2H2 zinc finger transcription factor WIP DOMAIN PROTEIN 2 (BnaWIP2) showed increased expression during the initial 12 hours of germination, and expression was further enhanced by salinity stress. Under NaCl treatment, knocking out all six BnaWIP2 paralogs in B. napus led to significantly reduced germination, while overexpression of BnaC06.WIP2 promoted germination. Transcriptomic analysis revealed that BnaC06.WIP2 downregulated a series of genes related to abscisic acid (ABA) biosynthesis and signaling, among which BnaA05.NCED3, BnaC04.ABI5-2, BnaA03.EM6, and BnaA05.EM6 were directly repressed by BnaC06.WIP2. Further analysis showed that in germinating seeds, BnaC06.WIP2 was induced by ABA and in turn restrained ABA production, indicating that BnaC06.WIP2 forms a negative feedback loop with ABA to promote seed germination under salinity stress in B. napus. Collectively, these results enhance our understanding of the novel function of BnaWIP2 and provide valuable genetic resources for breeding salinity-tolerant rapeseed varieties.